2018
DOI: 10.1364/boe.10.000104
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical basis of skin cancer margin assessment using Raman spectroscopy

Abstract: Achieving adequate margins during tumor margin resection is critical to minimize the recurrence rate and maximize positive patient outcomes during skin cancer surgery. Although Mohs micrographic surgery is by far the most effective method to treat nonmelanoma skin cancer, it can be limited by its inherent required infrastructure, including time-consuming and expensive on-site histopathology. Previous studies have demonstrated that Raman spectroscopy can accurately detect basal cell carcinoma (BCC) from surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…Previous studies have shown encouraging results for classifying nonmelanoma skin cancer versus normal tissue with Raman fiber probes [16][17][18][19][20][21]. Several studies have reported high sensitivity (63-100%) and specificity (83-91%) for discriminating the major types of nonmelanoma skin cancer, basal cell carcinoma (BCC), and squamous cell carcinoma (SCC) from normal skin in vivo [16,21,22] and ex vivo [23,24]. Though high diagnostic accuracy has been demonstrated in these studies, most used statistical algorithms to transform Raman spectra to a few significant dimensions, including principal component analysis [16,17,20,21], linear discriminant analysis [23], and maximum representation and discrimination feature [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown encouraging results for classifying nonmelanoma skin cancer versus normal tissue with Raman fiber probes [16][17][18][19][20][21]. Several studies have reported high sensitivity (63-100%) and specificity (83-91%) for discriminating the major types of nonmelanoma skin cancer, basal cell carcinoma (BCC), and squamous cell carcinoma (SCC) from normal skin in vivo [16,21,22] and ex vivo [23,24]. Though high diagnostic accuracy has been demonstrated in these studies, most used statistical algorithms to transform Raman spectra to a few significant dimensions, including principal component analysis [16,17,20,21], linear discriminant analysis [23], and maximum representation and discrimination feature [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…By selecting a balanced tumor score threshold, the specificity and sensitivity reached 94% and 82%, respectively. This ROC was then statistically compared to our recent study in 30 patients using R software to determine if the superpixel acquisition provides equivalent potential for BCC classification compared with the point‐by‐point scanning.…”
Section: Resultsmentioning
confidence: 99%
“…Bottom: SNR plot. The main bands of interest are assigned to collagen at 792, 942, 1056, 1269, 1454 and 1665 cm −1 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Raman microscopes have been developed with the intention of guiding surgery by assisting pathologists in the visualization of tissue margins in excised tissue (e.g., breast, 30 skin, 31 and oral 32 cancer). These systems can cover areas up to several , but they are unsuitable for performing molecular imaging in vivo .…”
Section: Introductionmentioning
confidence: 99%